Protective effect of bioaccessible fractions of citrus fruit pulps against H2O2-induced oxidative stress in Caco-2 cells. (January 2018) - Cilla, Antonio; Rodrigo, Maria J.; Zacarías, Lorenzo; De Ancos, Begoña; Sánchez-Moreno, Concepción; Barberá, Reyes; Alegría, Amparo
Abstract: Fruit pulps from Navel (N) and Cara Cara (CC) oranges, and Clementine mandarin freshly harvested (M) and refrigerated stored (M12) were used to evaluate the cytoprotective effect of their bioaccessible fractions (BF) against H2 O2 -induced oxidative stress in Caco-2 cells. BF of samples preserved viability vs. H2 O2 treated cells, reaching values similar to controls. Lipid peroxidation was reduced to levels of control cells, but M did not reach control values. ROS and mitochondrial membrane potential changes (Δψm ) values were reduced compared with H2 O2 treated cells, but without achieving control levels. A significant reduction in cell proportions in G1 phase and a significant increase in sub-G1 phase (apoptosis) of cell cycle was shown in H2 O2 treated cells, and BF allowed a recovery close to control levels. Thus, BF of samples protect the cells from oxidative stress by preserving cell viability, mitochondrial membrane potential and correct cell cycle progression, and diminishing lipid peroxidation and ROS. Graphical abstract: Highlights: Digested citrus pulps protect Caco-2 cells from H2 O2 -induced oxidative stress. Samples preserve viability, mitochondrial membrane potential and correct cell cycle. Digested citrus pulps decrease lipid peroxidation and ROS production. Cytoprotection of digested citrus pulps was independent of antioxidant activity. Citrus fruit pulps could prevent oxidative stress-related diseases.